Breeding for disease resistance in farm animals. (CABI, 2010)
The third edition of this book contains chapters that discuss the immune system and the genetic aspects of breeding livestock and fishes for increased resistance against viral, prion, bacterial, parasitic, vector-borne and metabolic diseases.